The contribution of economics to the analysis of climate change and uncertainty: a survey of approaches and findings - Sonja Peterson (Kiel Institute for World Economics (IfW), 2004)
There is a general agreement that (a) climate change is one of the most serious environmental problems, that (b) the analysis of climate change is confronted with a large degree of uncertainty and (c) that these uncertainties need to be taken into account to arrive at meaningful policy recommendations. The main contribution of economics to this interdisciplinary task is to provide formal frameworks and techniques for analyzing climate policy in the context of uncertainty. The aim of this paper is to give a comprehensive survey of existing approaches and findings and thus to give a broad picture of what economics has contributed and can contribute to the debate.
Keywords: C60; D83; Q54; D81; 330; Climate change; uncertainty; survey; modeling; Klimaschutz; Wirtschaftsmodell; Theorie; Welt